The prevalence of isolated hepatitis B core antibody and its related risk factors among male injected drug users in Isfahan prisons - Shirani, Kiana (Adv Biomed Res, 2015)
BACKGROUND: The prevalence of isolated hepatitis B core antibody (anti-HBc) varies between 1% and 30% in different populations. Isolated anti-HBc-positive patients who suffer from occult hepatitis B virus (HBV) infection have the potential to transmit HBV infection. So isolated anti-HBc screening is a valuable tool to prevent HBV transmission. Considering the importance of isolated anti-HBc screening and high prevalence of HBV among injected drug users (IDU) prisoners, we designed this study to evaluate the isolated anti-HBc positivity among inmates with the history of IDU in our area. MATERIALS AND METHODS: We did this cross-sectional study from September 2009 to March 2010 among volunteer male IDU prisoners in Isfahan. Blood samples were taken from all of subjects and tested for HBV markers. Then a questionnaire containing socio-demographic, drug histories and high risk behaviors information was completed for all participants. Data analysis was done utilizing univariate analysis and multiple logistic regressions. A P < 0.05 was considered significant. RESULTS: Totally 970 male IDU prisoners (mean age 32.6 ± 8.1) were included in our study. The prevalence of isolated HBc Ab was 4.5%. Isolated anti-HBc significantly was related to tooth filling (OR: 2.62, CI: 1.20-7.14) and imprisonment (OR: 3.95, CI: 1.39-11.18). We couldn’t find any relationship between isolated anti-HBc positivity and addiction duration, incarceration frequency, recent incarceration duration or number of injection per month. CONCLUSION: For screening high risk groups in parallel with hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (HBsAb) and other viral markers, maybe it is better to check HBcAb too, because isolated HBcAb-positive patients may have occult hepatitis B infection which could transfer the infection to others.